Aspekty etyczne systemów oceniania pracowników w instytucjach publicznych - Walenia, Alina (Annales. Etyka w Życiu Gospodarczym, 2015)
A performance appraisal system forms an integral part of any developed managementconcept. The efficiency of such an appraisal system is fostered in institutionswhich prioritise quality and continuous improvement, and where innovationfriendlyactions are joined by those that build confidence. An efficient appraisalsystem is characterised as follows: it is systemic in character, regular, universal,flexible, concrete, transparent and simple in application. When implementinga modern appraisal system, care should be taken to adhere to ethically sound principlessuch as fairness, objectivity, goodness and truthfulness.